Knowledge, attitude and behavior on utilizing suboptimal food related public health - Waode Dea Astria; Herdis Herdiansyah; Sri Setiawati Tumuyu (Intelektual Pustaka Media Utama, 2023)
Offering food products at lower prices approaching the expiration date, referred to as suboptimal food products, is considered to be able to encourage purchasing considerations by the public. It is based on knowledge of purchasing price-reduced food products by the public and the potential waste in the community focused. The study aimed to contribute to the evaluation of whether offering suboptimal foods at a lower price will reduce food waste in the supply chain. This study analyzes public knowledge, attitudes, and behavior toward suboptimal product price offers in retail stores. The research was conducted in three retail stores in Depok City by exploring research questions involving 274 retail store customers who were analyzed based on a questionnaire. The approach used is a quantitative approach with multiple linear analysis methods using SPSS software. The findings show that public knowledge, attitudes, and behaviors influence suboptimal product price offers in retail stores. This research is expected to be an effective solution to overcome excess food, which leads to food waste at the retail level in sustainable food management.